An air quality assessment in the industrialised western Bushveld Igneous Complex, South Africa - Andrew Venter; Ville Vakkar; Johan Beukes; Pieter van Zyl; Heikki Laakso; Desmond Mabaso; Petri Tiitta; Miroslav Josipovic; Markku Kulmala; Jacobus Pienaar; Lauri Laakso (South African Journal of Science)
South Africa has the largest industrialised economy in Africa, with significant mining and metallurgical activities. A large fraction of the South African mineral assets is concentrated in the Bushveld Igneous Complex (BIC), with the western limb being the most exploited. Because the majority of the world's platinum is produced in the BIC, this area is also of international interest. There are some indications that the western BIC should be considered an air pollution hotspot; however, inadequate data exist to substantiate these claims scientifically. To partially address this knowledge gap, a comprehensive air quality monitoring station was operated for more than 2 years in this area. Meteorological parameters, trace gas concentrations and total mass concentration of particulate matter up to 10 Âµm in size (PM10) were measured. Compared with South African and European ambient air quality standards, SO2, NO2 and CO concentrations were generally acceptable. The major sources of SO2 were identified as high-stack industry emissions, while household combustion from semi-formal and informal settlements was identified as the predominant source of NO2 and CO. In contrast, O3 exceeded the 8-h moving average more than 322 times per year. The main contributing factor was identified to be the influx of regional air masses, with high O3 precursor concentrations. PM10 exceeded the current South African 24-h standard 6.6 times per year, the future (2015) standard 42.3 times per year and the European standard more than 120 times per year. The main source of PM10 was identified as household combustion from semi-formal and informal settlements. The findings clearly indicate that atmospheric O3 and PM10 levels in the western BIC need to be addressed to avoid negative environmental and human health impacts.